Buenas prácticas agrícolas en los cultivos de maíz (zea mays l.) y maní (arachis hypogaea l.), en el cantón Rocafuerte. - Alava Saltos, Myrian Elena (2012)
The present study was conducted in three sites in the Manabí province Rocafuerte canton with the participation of three organizations: organization development ¨El Guarango¨, Association of farmers ¨Fe y Esperanza¨ and the women's organization ¨Nueva Vida”, in order that producers increase the productivity of crops of corn and peanut. In conjunction with the Provincial Council of Manabi (CPM) and the Agency Spanish for international cooperation for development (AECID), was carried out training in the management of good agricultural practices crop mentioned above. The tab of this information allowed to detect the percentage of participation of producers involved and interested in learning new technologies for these crops. The main objective of this work was transferring technology in the management and development of good agricultural practices in maize and peanut crops, establishing semi-advanced and plots of the producers which were used to obtain information and thus establish production quintals per hectare.